REPAIRSIN ENGLISH AND VIETNAMESE CONVERSATIONS - Assoc. Pro. Dr. Luu Quy Khuong (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study aims at finding out the features such as positions, strategies and functions of repairs in English and Vietnamese conversations to help the learners of English and Vietnamese to overcome the communication breakdowns during their conversations and help the teachers to build better speaking lessons.